IDDF2019-ABS-0310 Pattern of response to serial fecal microbiota transplantation via colonoscopic route in patients with ulcerative colitis. (June 2019) - Midha, Vandana; Mahajan, Ramit; Singh, Arshdeep; Mehta, Varun; Gupta, Yogesh; Kaur, Kirandeep; Narang, Vikram; Sood, Ajit
Abstract : Background: Fecal microbiota transplantation (FMT) targeting gut microbiome dysbiosis is an emerging therapy for ulcerative colitis (UC) and has been found to be efficacious in multiple randomized trials. However, there is no uniformity in protocols with respect to the route of administration, the frequency of intervention and amount of fecal slurry delivered. We intend to study the pattern of response to serial fecal microbiota transplantation via the colonoscopic route in patients with ulcerative colitis. Methods: A retrospective analysis of patients with active UC (Mayo clinic score ≥4), who received multi-session FMT (at weeks 0, 2, 6, 10, 14, 18 and 22) via a colonoscopic route, in addition to standard of care, between June 2015 and December 2018 was done. The proportion of patients maintaining steroid-free clinical remission (Mayo score ≤2, all sub scores ≤ 1) and achieving endoscopic remission (endoscopic Mayo score 0) were calculated for each FMT session. Results: One hundred twenty-four patients [mean age 34.84 ±11.91 years, 66.93% males (n=83), mean mayo clinic score 8.13 ± 2.65] who consented for FMT were analysed retrospectively. Proportion of patients maintaining steroid-free clinical remission (Mayo score ≤2, all sub scores ≤ 1)as well as achieving endoscopic remission (endoscopic Mayo score 0)increased with serial sessions of FMT (16.6% after 1 st session vs 65.55% after 7 th session for clinical remission and 3.62% after 1 st session vs 37.93% after 7 th session for endoscopic remission). (figure 1 ) Conclusions: With serial colonoscopic FMTs for active ulcerative colitis, the response rates, determined by the maintenance of steroid-free clinical remission and endoscopic remission, gradually increase. Repeated interventions over longer periods may result in a persistent change in gut microbiota composition that is otherwise inherently resilient, resulting in improvement in disease activity indices.